Neuroimaging evaluation in headache patients who have suffered a stroke or traumatic brain injury - Aragão, Maria de Fátima Viana Vasco; Araújo, Luziany Carvalho; Valença , Marcelo Moraes (Headache Medicine, 2022)
In a medical emergency, the most urgent patients at significant risk of death are those with a cerebrovascular accident and those with traumatic brain injury. Many are admitted with diminished conscience status (coma) and focal neurological deficits. In the evaluation of these patients, neuroimaging is indispensable in order to identify the type of lesion and the location of the brain where it is located. In the case of stroke, we can subdivide it into hemorrhagic and ischemic. Among hemorrhagic hemorrhages, we can mention (1) spontaneous intracerebral hematomas and (2) hemorrhages due to rupture of an intracranial aneurysm, with subarachnoid hemorrhage leading. Patients with head trauma are critical; even those who arrive at the hospital alert and oriented can decrease their level of consciousness in a few hours due to an intracranial hematoma, edema, or cerebral contusion. Thus, the availability of performing neuroimaging evaluations, using computed tomography and magnetic resonance imaging, or even digital angiography, is vital for continuous supervision of this type of patient. The exams often require repetition several times due to the rate of evolution of vascular lesions and after head trauma. A warning sign in these types of patients is headache. In the intracranial aneurysmal rupture, we classically have the thunderclap headache, an explosive, sudden pain mentioned as the worst pain the individual has suffered in his or her life. The pericranium and some intracranial structures are sensitive to nociceptive stimuli, such as the dura mater, large arteries, and venous sinuses. The brain is relatively insensitive to painful stimuli. This narrative review aims to inform the importance of neuroimaging assessment of patients with stroke and traumatic brain injury in an emergency department. In conclusion, a neuroimaging evaluation is paramount in addition to a neurological and physical examination of the critically ill patient with cerebrovascular disease or who has suffered a traumatic brain injury